KINETICS OF DIFFUSION-CONTROLLED EVAPORATION OF FE-MG OLIVINE: EXPERIMENTAL STUDY AND IMPLICATION FOR STABILITY OF FE-RICH OLIVINE IN THE SOLAR NEBULA - Ozawa K.; Nagahara H. (My University, 2000)
Evaporation is a process that caused chemical fractionation in the solar nebula. The evaporation rates of meteorite-forming minerals and silicate melts are key parameters for constraining the timescale of high temperature processes in the early solar nebula and for understanding the mechanisms of cosmochemical fractionation. The kinetics of evaporation of olivine (initial Fo = 92), the most common silicate in meteorites, was experimentally investigated at 1414°C for various duration under continuous evacuation. The surface of olivine becomes more magnesian and the interior becomes zoned as evaporation proceeds, indicating preferential evaporation of the fayalite (Fa) component. The weight loss, surface composition, and interior zoning profile were analyzed using a semi-infinite one-dimensional diffusion model with boundary migration, and the controlling model parameters were optimized by fitting the experimental results. The evaporation rate of olivine shows notable composition and orientation dependence. As olivine becomes more magnesian, the evaporation rates of the (100), (010), and (001) surfaces decrease, among which the rate at the (001) surface is greatest (1.0 μm/h at Fo = 91.8), which is about 2 orders of magnitude faster than that of pure synthetic forsterite. The estimated Fe-Mg fractionation factor shows anisotropy ranging from 0.017 to 0.035, which is significantly greater than the equilibrium value of the Fe-Mg distribution coefficient between olivine and gas, suggesting kinetic suppression of evaporation of the Fa component. The Fe-Mg interdiffusion coefficient at 1414°C, which also shows notable composition and orientation dependence, is estimated to be 8.7 x 10-15 m2/sec along the c-axis. The results were applied to constrain the timescale of heating for a spherical Fo50 olivine grain to retain the Fa component. Olivine dust ~1 μm in diameter can retain 80% of the initial Fa component for one minute in vacuum, and for ~30 min at ~10 Pa PH2 when heated at 1414°C. Therefore, Fo50 olivine in chondrite matrices could have survived an incipient heating event depending on the ambient hydrogen pressure, if they were originally present in the solar nebula.